Beauty confinement care / Nurul' Azizah Sulaiman - Sulaiman, Nurul' Azizah (Universiti Teknologi MARA, Sarawak, 2019)
After birth confinement period is a phase where the women will experience changes in their physical and emotional and transitioning to a new role as a mother. It started as soon as the baby being delivered and last up to 6 weeks where the mother's body will return to its nonpregnant state. During this period, postpartum women may experience few problems such as tiredness, gaining weight, constipation, haemorrhoids, and soreness of breasts as minor problems; to serious problems such as wound infections, pain, haemorrhage, psychosis and postpartum depression (PND). The essential features in the Malay postpartum care include the use of herbs, heat, and Malay postnatal massage (Akmal, 2015). This study was conducted to identify the problems in public health care services in handling pregnancy, birth and post-natal period; and to learn the services that customer needs for confinement care in Kuching, Sarawak. Data were obtained from interview questions from the customer of Surianitra Jelitia, that consist of part A, B, C, D and E on their experience with health care services and confinement care services. Problems in health care services is the understaffing and poor information provider, while the traditional Malay confinement care services is not being widely expose to the new generation and is not properly handle by the service provider. The market potential for a Bumiputera beauty and confinement care in Kuching is still presence especially for the traditional Malay confinement care and their nutrition needs. In term of financial, it is easy to get an incentive in the form of grants, capital needs, rental subsidiary through government institution or affiliate program; and loans from bank. Overall, the study of Malay traditional confinement care and beauty services is still relevant as it is still needed by pregnant ladies and mothers after giving birth. This is important as it helps mother to recovers to their pre-pregnancy state faster.